Design a nine-level modular multilevel converter for DC railway electrification system - Chuen Ling Toh; P. C. Ooi (Institute of Advanced Engineering and Science, 2020)
A recuperating converter is highly demanded in traction power substation to deliver the braking energy generated by a traction vehicle. Conventional voltage source inverter had been implemented in the traction power station. However, large ac line filters must be installed to improve the quality of ac voltages and currents. This paper proposes to install a nine-level Modular Multilevel Converter (MMC) as a recuperating converter. The main aim is to eliminate the need of ac line filters while producing good quality of ac voltage and current waveforms. The MMC is designed and modelled using MATLAB/Simulink Simulation tool. A centralized control of balancing all the sub-module capacitor voltage level is proposed with Third Harmonic Voltage Injection Level Shifted Pulse Width Modulation (THVI-LSPWM) technique. The simulation results prove that with the application of MMC, good quality of ac voltages and currents are being produced. The Total Harmonic Distortion indexes are found less than 3.5 % without using any ac line filters in the system. In addition, the classic DC link capacitance has also being eliminated.